ISOLASI DNA DAN AMPLIFIKASI PCR DAERAH ITS rDNA FUNGI ENDOFIT UMBI TANAMAN DAHLIA (Dahlia variabilis) LBKURCC69 - Fitri Rahayu; Saryono '; Titania Tjandrawati Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Endophytic fungi lives within healthy plant tissues without causing damage to the host plant. Endophytic fungi LBKURCC69 was one of the endophytic fungi that was isolated from the tubers of dahlia plant (Dahlia variabilis). Morphological identification showed that endophytic fungi LBKURCC69 was Phialophora fastigiata. This identification can’t provide an accurate result because many species of fungi with the same morphological features, that causing misidentification. More accurate species identification can be done by molecular identification using rDNA ITS region. Electrophoresis results indicated that chromosomal DNA of endophytic fungi LBKURCC69 was successfully isolated and has a molecular weight of 6124 bp. DNA amplification of endophytic fungi LBKURCC69 on rDNA ITS regions was successfully performed using ITS4 and ITS5 primers with 45°C annealing temperature and produces DNA fragments with a molecular weight of 537 bp.